Circadian and metabolic effects of light : implications in weight homeostasis and health - Plano, Santiago Andrés (2017)
Fil: Plano Santiago A. Universidad Católica Argentina. Facultad de Ciencas Médicas. Instituto de Investigaciones Biomédicas. Laboratorio de Cronofisiología; Argentina